Entrepreneurs Club: An eco-system for entrepreneurship and digital social innovation in the North Patagonia region, Argentina - Vivas, Héctor Luis (2018)
Fil: Vivas, Héctor Luis. Universidad Nacional de Río Negro. Laboratorio de Informática Aplicada. Río Negro. Argentina